Current state of tumour necrosis factor α blockade in Wegener's granulomatosis. (20th October 2005) - Mukhtyar, C; Luqmani, R
Abstract : Tumour necrosis factor α (TNFα) is likely to be involved in the pathogenesis of Wegener's granulomatosis. This paper reviews published clinical trials of the anti-TNFα agents etanercept and infliximab with regard to their efficacy and safety in the treatment of Wegener's granulomatosis. On the basis of the high rate of adverse events, particularly an increased incidence of cancers, the use of etanercept in the management of Wegener's granulomatosis is not justified. However, the potential role for infliximab or the as yet untested adalimumab cannot be discounted. The development of novel approaches focusing on blockade of specific molecules including TNFα in the treatment of Wegener's granulomatosis is awaited.